2003
DOI: 10.1046/j.1365-3083.2003.01244.x
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Bcl‐2 in T Cells Affects Insulitis in the Nonobese Diabetic Mouse

Abstract: The nonobese diabetic (NOD) mouse is a useful model for human autoimmune diabetes. The gene for the anti-apoptotic protein Bcl-2 has previously been suggested as a probable susceptibility candidate for the NOD mouse disease. In this study, we investigated how overexpression of Bcl-2 in lymphocytes might affect insulitis in NOD mice. A bcl-2 transgene expressed constitutively under the SV40-promoter and the 5 0 Igh enhancer, Em, was bred onto NOD background. Two bcl-2 transgenic NOD strains were produced and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
4

Year Published

2004
2004
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 38 publications
0
5
0
4
Order By: Relevance
“…Finally, it should be noted that the deficiency in Treg survival might be compounded by an independent genetic defect in Bcl-2 expression in NOD mice (Garchon et al, 1994). In fact, overexpression of Bcl-2 in T cells and B cells alleviated insulitis and conferred diabetes protection (Rietz et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it should be noted that the deficiency in Treg survival might be compounded by an independent genetic defect in Bcl-2 expression in NOD mice (Garchon et al, 1994). In fact, overexpression of Bcl-2 in T cells and B cells alleviated insulitis and conferred diabetes protection (Rietz et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that over-expression of Bcl-2 in both T and B cells leads to protection from insulitis in NOD mice [52]. There is also clinical support for this concept, since insulin-dependent diabetes mellitus (IDDM) patients show significantly reduced Bcl-2 expression in CD3+ and memory CD4+CD45RO+ populations and have higher levels of spontaneous apoptosis [53].…”
Section: Discussionmentioning
confidence: 99%
“…The histology score index was calculated by dividing the sum of all individual islet scores by the total number of islets evaluated. 51 Statistical analysis. Statistical analysis was performed using the Stata 8.2 (STATA, College Station, TX) software package, and the data collected were expressed as mean ± SEM.…”
Section: Flow Cytometric Analysis Of T-reg Cells In Mil-4-treated Nodmentioning
confidence: 99%